2021
DOI: 10.52152/spr/2021.152
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, concerns and support of physicians towards bio banks in Pakistan, and their willingness to donate

Abstract: Bio specimen collection and storage and bio bank data have numerous ethical issues. Stakeholders' views on these ethical problems are essential because they may assist establish ethical standards for bio banking. The aim of this research is to assess Pakistani doctors' views and knowledge regarding bio banking and willingness to donate. A cross-sectional online survey was conducted to poll Pakistani physicians’ attitudes and views regarding bio banks. Between January and April 2021.473 doctors completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…More importantly, medical students enrolled in this study were primarily motivated by the desire to help advance science and to develop innovative therapies (70.9%). Similar altruistic motivations were found in other countries, where both medical students and practicing physicians believed that donations would advance biomedical research and help to develop new diagnostic and therapeutic methods [ 44 , 47 , 48 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…More importantly, medical students enrolled in this study were primarily motivated by the desire to help advance science and to develop innovative therapies (70.9%). Similar altruistic motivations were found in other countries, where both medical students and practicing physicians believed that donations would advance biomedical research and help to develop new diagnostic and therapeutic methods [ 44 , 47 , 48 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 61%
“…Thus, our research confirms that there is an urgent need to broaden MS’ knowledge about biobanks, since limited awareness of biobanks, their role and their activity was also found among practising HCPs. In fact, irrespectively from the country, previous studies demonstrated that HCPs in Australia, Colombia, Côte d’Ivoire, Morocco, Saud Arabia, Egypt, Pakistan either had never heard about biobanks and did not know the existence of biobanks in their countries, or did not understand properly their role and the purpose of biobanks, and were unfamiliar with biobanking Standard Operating Procedures (SOPs) [ 37 , 39 , 43 , 44 , 63 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial workbenches, such as DN Anexus These providers also support APIs that allow users to launch automated large batch analyses without using a Web interface. [14][15][16] Next-generation cloud-based open source workbenches, such as Curoverse's Arvados (https://curo verse.com) and the iPlant Collaborative's Agave, largely dispense with the Web GUI as a primary design tool and instead are built from the ground up as APIs designed to enable the migration of local analyses to the cloud for collaborative research. [14][15][16]…”
Section: Cloud Workbenches and Apismentioning
confidence: 99%